2007
DOI: 10.1029/2007gb002934
|View full text |Cite
|
Sign up to set email alerts
|

Flux and age of dissolved organic carbon exported to the Arctic Ocean: A carbon isotopic study of the five largest arctic rivers

Abstract: [1] The export and D 14 C-age of dissolved organic carbon (DOC) was determined for the Yenisey, Lena, Ob', Mackenzie, and Yukon rivers for [2004][2005]. Concentrations of DOC elevate significantly with increasing discharge in these rivers, causing approximately 60% of the annual export to occur during a 2-month period following spring ice breakup. We present a total annual flux from the five rivers of $16 teragrams (Tg), and conservatively estimate that the total input of DOC to the Arctic Ocean is 25-36 Tg, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

51
613
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 477 publications
(679 citation statements)
references
References 45 publications
51
613
3
Order By: Relevance
“…This separates these subarctic catchment-stream systems from Scandinavian boreal forest streams, for which previous reports have shown that DIC accounts for only about 19 % of the total C export (Wallin et al, 2010). A similar proportion of DIC to the total C flux is also found in the large Siberian Rivers, especially in the east (data in Raymond et al, 2007 andTank et al 2012) and Alaskan rivers . A comparison of literature values from permafrost-affected catchments in high-latitude areas ( Table 5) also suggest that the concentration values we report for DOC are roughly within the same range as other permafrost-affected streams/rivers in high-latitude areas whereas our DIC concentrations seem to be in the lower range of the reported values (Table 5).…”
Section: The Relationship Between Doc and Dic Concentrations And Fluxesmentioning
confidence: 49%
“…This separates these subarctic catchment-stream systems from Scandinavian boreal forest streams, for which previous reports have shown that DIC accounts for only about 19 % of the total C export (Wallin et al, 2010). A similar proportion of DIC to the total C flux is also found in the large Siberian Rivers, especially in the east (data in Raymond et al, 2007 andTank et al 2012) and Alaskan rivers . A comparison of literature values from permafrost-affected catchments in high-latitude areas ( Table 5) also suggest that the concentration values we report for DOC are roughly within the same range as other permafrost-affected streams/rivers in high-latitude areas whereas our DIC concentrations seem to be in the lower range of the reported values (Table 5).…”
Section: The Relationship Between Doc and Dic Concentrations And Fluxesmentioning
confidence: 49%
“…They are strongly impacted by the input and transformation of terrestrial OM Dudarev et al, 2006;Gustafsson et al, 2011;Mann et al, 2012Mann et al, , 2015Semiletov et al, 2007Semiletov et al, , 2016Tesi et al, 2016;Bröder et al, 2016;. The input of suspended as well as dissolved terrigenous material (Alling et al, 2010;Raymond et al, 2007;Holmes et al, 2012) including optically active fractions of dissolved OM, colored dissolved OM (CDOM; Pugach et al, , 2017, and the presence of ice cover throughout a significant part of the year reduces the depth of solar radiation penetration into the water column. Together with limited nutrient content, these conditions make these seas unproductive, 5-10 times less productive than inflow shelves (Carmack et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This emphasizes the role of the riparian zone as a source of DOC in lakes and streams, since during the transport from deeper forests carbon is either respired or adsorbed before it enters water bodies. Isotopic studies have also demonstrated that most of the carbon entering streams is young (Raymond et al 2007). …”
Section: Discussionmentioning
confidence: 99%